2018
DOI: 10.1111/hepr.13197
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of portal vein pressure gradient under different degrees of liver cirrhosis and resection volume in the first week post hepatectomy

Abstract: The increase in PVPG following LR was positively associated with the degree of cirrhosis, significantly peaking on POD 3. The LR volume only had a significant impact on PVPG for patients with moderate and severe cirrhosis. This represents the first time, to our knowledge, that dynamic changes of PVPG after LR were measured and compared to cirrhosis and resection volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Notably, a gradual decrease in the portal vein pressure gradient was observed during the follow-up period in most patients in concordance with liver regeneration and volume increase. 26 As shown in a recent study, the percentage of patients who underwent hepatic resection for liver tumors accompanied by postoperative splenomegaly was only 16.4% at 3 years after hepatectomy, although more than half of the patients still had incomplete liver restoration. 27 These results suggest that the portal vein pressure of most patients gradually recovers to the preoperative level, accompanied by liver regeneration and remodeling in the late postoperative period.…”
Section: Variablesmentioning
confidence: 89%
See 2 more Smart Citations
“…Notably, a gradual decrease in the portal vein pressure gradient was observed during the follow-up period in most patients in concordance with liver regeneration and volume increase. 26 As shown in a recent study, the percentage of patients who underwent hepatic resection for liver tumors accompanied by postoperative splenomegaly was only 16.4% at 3 years after hepatectomy, although more than half of the patients still had incomplete liver restoration. 27 These results suggest that the portal vein pressure of most patients gradually recovers to the preoperative level, accompanied by liver regeneration and remodeling in the late postoperative period.…”
Section: Variablesmentioning
confidence: 89%
“…These structural changes would contribute to arterial hypoperfusion and pathological increases in intrahepatic vascular resistance, further increasing portal pressure 7,28 . Scarring in the cirrhotic liver leads to a reduction in elasticity and an increase in stiffness, which further contributes to an increased portal vein pressure gradient following liver resection 26 . Therefore, more attention should be paid to the possibility of PHPH in high‐risk patients with HBV infection, cirrhosis, or elevated ALT levels, and the use of drugs to decrease portal pressure should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study reported by Lan et al, PVP and CVP were measured every day for a week after hepatectomy through portal and central vein catheterization [30]. It was found that PVPG was affected by extent of resection only in patients with moderate and severe cirrhosis.…”
Section: Discussionmentioning
confidence: 99%